(untitled) (Biological Sciences - PJSIR, 2003)
Aminopyranodioxin derived from benzophenone isomerize to yield 6 substituted 1, 2-dihydropyridodioxins (III),whose structures were determined by chemical conversions and spectroscopic studies.